A Review of Various Encryption Techniques (International Journal of Engineering and Computer Science, 2014)
In today’s world secure transmission of important or personal data is of big concern. The encryption of the data plays important factor of security while sending the information of data. Encryption of data means converting plain text to cipher text. There are many encryption techniques available, but the big question that arises is which one is good one or which one is suitable as per requirements. In this paper we do analysis of various encryption techniques viz. AES, BLOWFISH, DES, 3DES, RC4, RC6, RSA, UMARAM and UR5.